Obesitas Sentral terhadap Kadar Gula Darah Postprandial pada Pegawai Laki-Laki Dewasa di Lingkungan Kerja - Andini Bakti Putri; Anita Anita (Politeknik Kesehatan Tanjung Karang, 2019)
Type 2 diabetes patients as much as 80% are overweight (obese). The obesity rate in Lampung province is 8.7%. The lowest prevalence of central obesity is 2.2% in North Lampung and 35.9% is highest in Metro city. Obesity causes changes in body cells to become resistant to the hormone insulin, so that blood levels increase. The effect of it is that insulin-producing cells work harder and become gradually damaged, these are the reason that causes an increase in the number of diabetics. The purpose of this study to determine the relations of central obesity to postprandial blood glucose levels in adult male employees at Lampung University. This research used a cross-sectional approach. The sample of this research is all male employees of Lampung University with ages of 26-45 years determined by consecutive sampling. 65 respondents like to check postprandial blood glucose levels. The data were analyzed by using the Chi-Square test. Most of the respondents had abnormal postprandial blood glucose levels (67.7%) than respondents who had normal postprandial blood glucose levels (32.3%). Based on bivariate analysis with the Chi-square test, the relation of central obesity and postprandial blood glucose levels in male adult employees in Lampung University with a p-value of 0.001. There is a relationship between central obesity in adult male employees and postprandial blood glucose levels at Lampung University.